Bacterial adhesion performance of poly (tetrafluoroethylene) after surface modification using hydrogen and oxygen low-energy gas discharges - Salapare, Hernando S. III
The bacterial adhesion performance of polytetrafluoroethylene (PTEE) materials is determined using contact angle measurements, scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), Esherichia coli (E.coli) adhesion tests, and surface free energy calculations. PTFE samples are irradiated using hydrogen and oxygen low-energy gas discharges using a gas discharge ion source (GDIS) facility with ion energies varied by changing the plasma discharge current (Id) at intervals of 1mA from 1mA to 3mA. Results show that both the hydrogen and oxygen plasma different Id, hydrogen treatment shows that lower Id improved material hydrophobicity and higher Id resulted in enhanced hydrophobicity, while oxygen treatment shows that as the Id increases, PTFE becomes more hydrophilic. The contact angle degrades within the range of 1.4ᵒ to 7.4ᵒ in 210 days after treatment. The hydrogen and the oxygen treated PTFE exhibited a reduced E. Coli attachment on the samples. Oxygen treatment exhibited a lower E. coli adhesion as compared to using hydrogen. The optimum range of surface free energy taht exhibited the lowest E. coli adhesions is between 22mN/ m to 26 mN/n.